ANALISIS USAHATANI TANAMAN HIAS DI KOTA KENDARI - Syarni, Pertiwi; Padangaran, Normal Bivariant; Nur, Hartatia; Purwanti, Rahayu Endah; Ningsih , Minggu Lestari; Yusriadin, Yusriadin (Jurusan Penyuluhan Pertanian FP UHO, 2026)
The economic potential of ornamental plant farming in Kendari City is significant, given the rapid urban development and increasing market demand. However, the sector faces challenges related to production costs, business management, technology, and capital. The objective of this study is to analyze the practices and economic implications of ornamental plant farming in Kendari City. The research method employed is a survey method with a case study approach. The research population consists of all ornamental plant cultivation businesses in Kendari City, with a sample size of 25 people. The data was analyzed using a quantitative descriptive approach. The results indicate that the commercial cultivation of ornamental plants in Kendari City is economically viable and lucrative. In the context of horticultural enterprises, production costs are predominantly influenced by labor expenditures, particularly in the context of fertilization activities. This observation is indicative of the inherently labor-intensive nature of horticultural business operations. The age of the crop has been demonstrated to exert a substantial influence on revenue generation. Specifically, 4-month-old plants have been observed to yield higher revenue compared to 2-month-old plants, despite the extended production time associated with the former. The mean net income from ornamental plant farming is IDR 48,703,974 per cycle, or IDR 12,175,993 per month, indicating a high level of profitability. Ornamental plant farming possesses the potential to become a sustainable urban agribusiness in Kendari City.